2001
DOI: 10.1002/jez.1080
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal regeneration in masculinized female or steroid‐treated rainbow trout (Oncorhynchus mykiss)

Abstract: In salmonids, the development of an indifferent gonad into a testis or an ovary is normally determined chromosomally but can be reversed or changed by the administration of exogenous steroids during specific times in embryonic development. Because the gonads of sexually mature rainbow trout (RBT) are capable of regeneration following surgical removal and since regeneration of some tissue involves dedifferentiation, the objective of this experiment was to determine if the phenotypic sex of RBT gonads could be r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…For example, attempts to sterilize Chinese grass carp by surgical ovariectomy were largely unsuccessful, due to subsequent ovarian regeneration, possibly due to the presence of remaining ovarian tissue (Underwood et al, 1986). Similar experiments in rainbow trout have shown that ovarian regeneration following ovariectomy also occurs due to amplification of remaining gonadal tissue, as complete gonadectomy results in sterility (Kersten et al, 2001). Likewise, complete ovariectomy of Betta splendens resulted in gonadal regeneration and occasional female to male sex reversal, suggesting the existence of a bipotential germline stem cell (possibly extra-ovarian) underlying gonadal regeneration (Lowe and Larkin, 1975).…”
Section: Introductionmentioning
confidence: 70%
“…For example, attempts to sterilize Chinese grass carp by surgical ovariectomy were largely unsuccessful, due to subsequent ovarian regeneration, possibly due to the presence of remaining ovarian tissue (Underwood et al, 1986). Similar experiments in rainbow trout have shown that ovarian regeneration following ovariectomy also occurs due to amplification of remaining gonadal tissue, as complete gonadectomy results in sterility (Kersten et al, 2001). Likewise, complete ovariectomy of Betta splendens resulted in gonadal regeneration and occasional female to male sex reversal, suggesting the existence of a bipotential germline stem cell (possibly extra-ovarian) underlying gonadal regeneration (Lowe and Larkin, 1975).…”
Section: Introductionmentioning
confidence: 70%
“…In many species and in the tilapias in particular, a partial or total regeneration of the gonads, probably resulting from remaining small fragments of the terminal parts of the gonads, has sometimes been observed after castration (McLean, 1994; Toguyeni, 1996; Kersten et al ., 2001). The plasma oestradiol concentrations (E2) were measured to confirm the effectiveness of the gonadectomy and the degree of regeneration of the gonads.…”
Section: Methodsmentioning
confidence: 99%
“…The plasma concentrations of oestradiol were used to check the effectiveness and the impact of castration. In practice, in tilapia, as in many fish species, surgical castration is often followed by partial or total regeneration of the gonads (Kersten et al ., 2001). The somatic growth and the condition factors were used to measure the impact of the different treatments to relate them to the growth of the otolith.…”
Section: Introductionmentioning
confidence: 99%
“…44 Similarly, ovariectomy is followed by ovarian regeneration in rainbow trout. 45 Recently, using a zebrafish transgenic model for selective oocyte ablation during adulthood, White and colleagues demonstrated that targeted elimination of oocytes leads to a rapid degeneration of the ovary, although the ovarian remnants still contained oocyte precursor cells and somatic cells. 46 When the animals were allowed to recover, not only did oocytes regenerate and repopulate the ovary, but the somatic cells differentiated into follicular cells and continued to participate in follicle formation.…”
Section: Oogenesis In Adult Fliesmentioning
confidence: 99%